2018
DOI: 10.1111/jfr3.12334
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater flooding in a river‐connected alluvial aquifer

Abstract: Groundwater flooding can occur when the water table rises due to (a) recharge to (or decreased abstraction from) aquifers with low storativity or (b) propagation of the rising river stages into permeable, river‐connected alluvial aquifers. The latter type was significant in 2013 in Alberta. A survey of 189 homes along the Elbow River in Calgary examined the basement flooding water characteristics and the initial route of floodwater entry. In homes where the initial route of entry was known, 88% were initially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…Rising water tables can lead to the presence of groundwater near residential foundations which can increase basement flood potential and damage to the foundation (Soren, 1976). This was recently observed in the Alberta 2013 floods where increases in the river stage lead to rising groundwater levels in riverconnected aquifers, leading to occurrences of infiltration flooding into basements (Abboud et al, 2018). Changes in groundwater abstraction rates and practices have also led to documented cases of rising groundwater levels and concern regarding the impact on infrastructure (Wilkinson, 1985).…”
Section: Environmental Factorsmentioning
confidence: 97%
“…Rising water tables can lead to the presence of groundwater near residential foundations which can increase basement flood potential and damage to the foundation (Soren, 1976). This was recently observed in the Alberta 2013 floods where increases in the river stage lead to rising groundwater levels in riverconnected aquifers, leading to occurrences of infiltration flooding into basements (Abboud et al, 2018). Changes in groundwater abstraction rates and practices have also led to documented cases of rising groundwater levels and concern regarding the impact on infrastructure (Wilkinson, 1985).…”
Section: Environmental Factorsmentioning
confidence: 97%
“…While probabilistic and empirical approaches have contributed to the development of regional groundwater flood maps (Cobby et al, 2009;Jacobs, 2007), physically-based models are scarce. Abboud et al (2018) found that the June 2013 compound flood disaster in the Elbow River (Canada) was induced by steady precipitation and increased river flow discharges from upstream basins resulting in basement flooding due to the rise of the water table. The combined effects of fluvial and groundwater flooding were not considered on that study since the MODFLOW river package focused exclusively on groundwater flow.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, uncontrolled seepage may result in a hazard both to flood protection elements and to the subsurface parts of structures like cellars, subsurface garages, and so on in the territory protected against flooding (MacDonald, Dixon, Newell, & Hallaways, 2012). The threat is posed by the pressure of subsurface water on the inundation and subsurface infrastructure (Abboud, Ryan, & Osborn, 2017; Kreibich & Thieken, 2008), namely underground parts of civil structures, and by the high hydraulic gradients along the foundations of flood protection elements and at places of groundwater leakage onto the ground surface. Seepage into the protected area is also unfavourable during a flood as it increases the amount of “internal waters” that must be pumped back into the stream.…”
Section: Introductionmentioning
confidence: 99%